A little book of alliterations - Arthur, Felix; Capon, Jenny ([Cheltenham, Gloucestershire, England] : Inside Pocket Pub., 2010)
Presents an imaginative and artistic interpretation of the letters of the alphabet using alliterative verse.
"This book should be read aloud ..."
Keywords: Alphabet books -- Juvenile literature; Alliteration -- Juvenile literature; Nonsense verses; Alphabet; Alliteration; Nonsense verses; Alphabet; Nonsense verses